HUBUNGAN POLA KONSUMSI ZAT BESI TERHADAP KEJADIAN ANEMIA PADA ANAK USIA SEKOLAH - Dhyta " Puspita; Riri " Novayelinda; Wasisto " Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstrack Anemia is the most founded health problem in developing country. The most founded anemia’s problem was in children that caused by iron deficiency. The aim of this study was to identify the correlation between diet consumption pattern toward anemia among school age children in Sail, Pekanbaru. The design of this study was descriptive correlation with cross sectional approach. This study involving 30 school age children that taken with using snowball sampling technique and selected based on inclusion criteria. This study used Semiquantitative Food Frequency Questionnaire for taking consumption pattern from the children and digital haemoglobin test device for taking the haemoglobin value. The univariate analysis was conducted to knowing the distribution of respondent and the bivariate used Fisher Exact. The study result showed that from 11 respondents with iron consumption pattern same with the standard, as many as 9 respondents not had anemia (30,0%) and 2 respondents had anemia (6,7%). From 19 respondents that had iron consumption pattern not same as the standard, 1 respondents among it not had anemia (3,3%) and 18 respondents had anemia (60,0%). Fisher Exact analysis result showed that p value (0,000) < α (0,05), which means that there is correlation between diet consumption pattern toward anemia in school age children. Keywords: School age children, anemia, diet consumption pattern, iron